Arthropod-borne diseases among travellers arriving in Europe from Africa, 2015 to 2019 - Gossner, Céline M; Hallmaier-Wacker, Luisa; Briet, Olivier; Haussig, Joana M; de Valk, Henriette; Wijermans, Ariana; Bakonyi, Tamas; Madubuko, Theresa; Frank, Christina; Noel, Harold; Abdulaziz, Mohammed (Euro surveillance : bulletin européen sur les maladies transmissibles, 2023)
BackgroundTravellers are generally considered good sentinels for infectious disease surveillance.AimTo investigate whether health data from travellers arriving from Africa to Europe could provide evidence to support surveillance systems in Africa.MethodsWe examined disease occurrence and estimated risk of infection among travellers arriving from Africa to Europe from 2015 to 2019 using surveillance data of arthropod-borne disease cases collected through The European Surveillance System (TESSy) and flight passenger volumes from the International Air Transport Association.ResultsMalaria was the most common arthropod-borne disease reported among travellers from Africa, with 34,235 cases. The malaria travellers' infection rate (TIR) was 28.8 cases per 100,000 travellers, which is 36 and 144 times higher than the TIR for dengue and chikungunya, respectively. The malaria TIR was highest among travellers arriving from Central and Western Africa. There were 956 and 161 diagnosed imported cases of dengue and chikungunya, respectively. The highest TIR was among travellers arriving from Central, Eastern and Western Africa for dengue and from Central Africa for chikungunya in this period. Limited numbers of cases of Zika virus disease, West Nile virus infection, Rift Valley fever and yellow fever were reported.ConclusionsDespite some limitations, travellers' health data can efficiently complement local surveillance data in Africa, particularly when the country or region has a sub-optimal surveillance system. The sharing of anonymised traveller health data between regions/continents should be encouraged.